Cancer as the "perfect storm"? A qualitative study of public attitudes to health conditions. Issue 1 (27th October 2017) - Morrell, Liz; Ii, Suzanne Sayuri; Wordsworth, Sarah; Wilson, Roger; Rees, Sian; Barker, Richard
Abstract: Aims: Our aim is to identify important attributes of major diseases that shape how they are perceived by the public. Methods and Results: Four focus groups among members of the public were recruited, in March and October 2016, and used semistructured discussion to explore important attributes of cancer, heart disease, stroke, dementia, mental illness, and infectious disease. Common themes were identified by using inductive thematic analysis. Five themes were identified: fear, impact on family and friends, hope, detection, and prevention. Fear of cancer includes not only fear of death but also of aggressive treatments. Loss of dignity is feared in dementia, while infectious disease raises fear of uncontrollable "plague"; in contrast, people with mental illness may themselves be seen as a potential threat. The impact of cancer and its treatment on family and friends was described as intense and all‐consuming, even for those not involved directly in caring; with dementia and stroke, the family impact is taking on care, including funding, over the long term with little expectation of improvement. Hope is a major theme in cancer and stroke recovery, linked with the need to take action, often expressed in aggressive language of "fighting, " but seen as futile in dementia. Detection difficulties for "silent" cancers mean that real treatment opportunities are missed; cardiovascular and infection risk, however, are seen as easy to identify and act on, whereas mental illness and dementia are seen as poorly diagnosed and with limited treatment options. Prevention awareness is high for cardiovascular disease and infection, lower for cancer, and limited for dementia and mental health. Conclusion: Although themes overlap across diseases, the specific concerns are different and each condition has a unique profile. Quantifying the relative importance of these themes could allow their incorporation in decision‐making, not only when they occur as a named disease but also in any relevant condition. Abstract : This qualitative study aimed to identify important attributes of major illnesses that shape how they are perceived by the public. Our results identified 5 common themes: fear, impact on family and friends, hope, detection, and prevention. Although the themes overlapped across the 6 health conditions discussed, the specific concerns differed, with each condition showing a unique profile and pattern of overlaps with the others.